2010
DOI: 10.1002/app.31597
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of electrospinning an SU‐8 negative photoresist to create patterned carbon nanofibers and nanobeads

Abstract: The optimization of electrospinning SU-8 2100 negative photoresist was performed to create carbon micro/nanofibers and beads that can be patterned after electrospinning by using UV radiation. The fiber diameters had a range of 300 nm to 1 lm, based upon the selected electrospinning parameters. Low concentrations of the SU-8 2100 resulted in beads while specific higher concentrations produced well-defined fibers. Fibers and beads were converted to carbon through pyrolysis and retained their three dimensional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…6,19,25 However, in other cases, lower voltages result in a decrease in fiber diameter due to the reduced acceleration of the jet and weaker electric field, which increases the time of flight of the jet allowing for more fiber stretching. 19,26,27 In such instances, to obtain thinner fibers, voltages closer to the critical voltage would be advantageous. At applied voltages lower than 8 kV, electrospraying occurs, while at an applied voltage of 8 kV, near the critical voltage, the "beads on a string" morphology is observed.…”
Section: Effect Of Applied Voltagementioning
confidence: 99%
“…6,19,25 However, in other cases, lower voltages result in a decrease in fiber diameter due to the reduced acceleration of the jet and weaker electric field, which increases the time of flight of the jet allowing for more fiber stretching. 19,26,27 In such instances, to obtain thinner fibers, voltages closer to the critical voltage would be advantageous. At applied voltages lower than 8 kV, electrospraying occurs, while at an applied voltage of 8 kV, near the critical voltage, the "beads on a string" morphology is observed.…”
Section: Effect Of Applied Voltagementioning
confidence: 99%
“…The following protocol was developed to produce beads as suggested by Steach et al [13] with a size distribution comprised between 100 and 500 nm as found on the Pieris rapae butterfly. According to Sharma et al [14] low viscosity polymers solutions (SU-8 2002 and 2005 from Microchem, Newton, MA, USA) were used to produce the beads.…”
Section: Fabrication Of Mie Scatterersmentioning
confidence: 99%
“…The parameters for the optimization of electrospinning SU-8 were previously investigated and were applied here to generate the fiber coating. 30…”
Section: Current Researchmentioning
confidence: 99%
“…The optimized conditions used to make the SU-8 nanofibers produced a mat composed of solid fibers with diameters of ~ 400 nm. 30 The structure of the mat provides a porous network for extractions and the fibers provide a high surface area. An electrospinning time of 30 seconds was initially chosen to characterize the extraction properties of both the SU-8 2100 and the pyrolyzed SU-8 electrospun-fiber coated wires as a novel SPME fiber coating.…”
Section: Electrospun Spme Fiber Preparationmentioning
confidence: 99%